Analisis Penetapan Pengadilan Agama Mengenai Itsbat Nikah Dalam Perspektif Kompilasi Hukum Islam - Hidayat, Rahmat; Hasriyanti, Hasriyanti; Muharuddin, Muharuddin (Journal of Law Justice (JLJ), 2023)
This study aims to determine the legal analysis of Marriage Itsbat and the analysis of the determination of the Sorong Religious Court No.126/Pdt.P/2022/PA.Srog. The research method used is Normative legal research method by analyzing legal materials through literature study. Based on the results of the research, although Islamic Law does not implicitly recommend the registration of each marriage, but through the Compilation of Islamic Law (KHI) in article 5 KHI states that marriage registration needs to be done to ensure order in marriage. As for marriages that are not registered in accordance with the provisions of Presidential Instruction 1 of 1991 concerning the Compilation of Islamic Law in Article 7 paragraph (2) KHI, the process of applying for Itsbat Nikah through the Religious Court can be carried out. As an example of a case in the determination letter of the Religious Court judge No.126 / Pdt.P / 2022 / PA.Srog, the judge's determination in legalizing the Application for marriage Itsbat  of Applicants I and II is correct because it is in accordance with the legal requirements and pillars of marriage in Islamic law without any obstacles to the marriage of the two applicants. Points such as the position of one of the applicants II as a Civil Servant (PNS) can also be considered by the judge as one of the urgencies so that the Applicant applies for Marriage Itsbat.